Deelnemen aan de beoordeling van het veiligheids- en preventiebeleid. Tests met burgerparticipatie in Brussel - Valérie Caprasse (Brussels Studies, 2023)
This article is based on empirical material consisting of focus groups conducted with professionals involved in the evaluation of municipal prevention services as well as with Brussels citizens, and looks at some of the issues regarding citizen participation in the evaluation of security and prevention policies in the Brussels Region. On the one hand, the very nature of these policies raises ethical questions which call for procedural guarantees in keeping with the wishes of professional stakeholders. On the other hand, the absence of certain profiles of the population within the Brussels participatory mechanisms raises questions among professional stakeholders and leads to the formulation of ways to move towards more inclusive processes – both by the evaluators and by the citizens interviewed. Finally, the production of new knowledge through citizen participation is also at the heart of the issues identified.